Survival Outcomes of Lung Adenocarcinoma With Intestinal Differentiation in the Era of Immunotherapy - Micah Tratt, BA; Anshu Bandhlish, MD; Keith D. Eaton, MD, PhD; Ted Gooley, PhD; Nicholas Giustini, MD; Lei Deng, MD (JTO Clinical and Research Reports)
Introduction: Lung adenocarcinoma (LUAD) with intestinal differentiation (LAID) comprises a rare and heterogeneous NSCLC of invasive mucinous, enteric, and colloid characteristics. In the era of chemotherapy, LAID was associated with a poorer prognosis compared with other LUADs. Leveraging the National Cancer Database, we assessed survival outcomes of LAID in the era of immunotherapy. Methods: The National Cancer Database was queried for stage IV adenocarcinoma cases diagnosed from 2016 to 2019. LAID was defined as invasive mucinous adenocarcinoma, colloid adenocarcinoma, or enteric adenocarcinoma. An unadjusted comparison of survival distributions was performed using a log-rank test and adjusted by Cox multivariable regression. Results: A total of 40,516 patients were identified, of whom 855 had LAID and 39,661 had other LUAD. Among the cases of LAID, 593 were classified as colloid, 253 as mucinous, and nine as enteric. Patients with LAID had a higher risk of death compared with other LUAD subtypes, with a hazard ratio (HR) of 1.31 (95% confidence interval: 1.21–1.43) and a median survival of 9.19 months and 11.81 months, respectively. This was relatively consistent across all treatment subgroups (HR = 1.40: immunotherapy alone, HR = 1.29: chemoimmunotherapy; HR = 1.25: chemotherapy alone). Patients with LAID treated with chemoimmunotherapy had a median overall survival of 11.16 months, 9.19 months when treated with immunotherapy alone, and 7.09 months when treated with chemotherapy alone. Conclusions: Compared with other LUADs, LAID remains associated with poorer survival in the era of immunotherapy. Nevertheless, exposure to immunotherapy may be associated with improved survival compared with chemotherapy alone in this rare subgroup.